A systematic review and thematic synthesis exploring how a previous experience of physical activity influences engagement with cardiac rehabilitation. (1st January 2020) - McHale, Sheona; Astin, Felicity; Neubeck, Lis; Dawkes, Susan; Hanson, Coral L
Abstract: Background: Exercise-based cardiac rehabilitation is recognised internationally as an effective therapy to improve quality of life and reduce the risk of hospital readmission for individuals diagnosed with acute coronary syndrome. Despite this, half of eligible individuals choose not to engage and the main reason is lack of interest. Furthermore, prior to attending, 40% of eligible individuals report meeting physical activity guidelines. It is unclear whether this influences decisions about engagement. Aims: The aim of this review is to examine systematically qualitative evidence describing patients' perceptions and experiences, and synthesise what is known about how a previous experience of physical activity in adults diagnosed with acute coronary syndrome influences engagement with physical activity during cardiac rehabilitation. Methods: A systematic review and thematic synthesis was conducted of primary qualitative studies to examine peer-reviewed literature published between1990 and 2017, accessed from database searches of MEDLINE, CINHAL, PsycINFO and Embase. Results: The initial search produced 486 studies, and of these 12 relevant studies were included in this review. Studies included 388 participants from six countries. For previously active individuals, communication factors, self-perceptions of an exercise identity and experience of cardiac rehabilitation influence engagement in physical activity during cardiac rehabilitation. Conclusion: In adults diagnosed with acute coronary syndrome, communication post event and during cardiac rehabilitation is a source of self-appraisal and creates expectations of cardiac rehabilitation. In addition, perceptions of an exercise identity and experience of exercise-based cardiac rehabilitation influence decisions about engagement. To improve uptake and adherence, health professionals should consider previous physical activity levels and tailor information to optimise physical activity post event.